2022
DOI: 10.1186/s10195-021-00620-9
|View full text |Cite
|
Sign up to set email alerts
|

Addition of shock wave therapy to nail dynamization increases the chance of long-bone non-union healing

Abstract: Background Long-bone non-unions after intramedullary nailing can be treated by nail dynamization or focused high-energy extracorporal shock wave therapy (fESWT). The objective of this study was to assess the effect of the combination therapy of nail dynamization and fESWT on long-bone non-unions. Materials and methods 49 patients with long-bone non-unions (femur and tibia) after nailing were treated with nail dynamization (group D, n = 15), fESWT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Alvarez performed ESWT in 34 fractures in 32 metatarsal non-union patients at an average of 23 weeks after injury and reported the bone union rate as 89% after an average follow-up of 1 year [ 21 ]. Josef et al performed ESWT in 17 long-bone (tibia-femur) pseudoarthrosis patients and had a bone union rate of 64.7% [ 22 ]. Zelle reported had a 76% bone union rate, which was higher in the hypertrophic pseudoarthrosis in the 10 studies including 924 delayed unions treated with ESWT they reviewed to assess the efficacy of ESWT [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alvarez performed ESWT in 34 fractures in 32 metatarsal non-union patients at an average of 23 weeks after injury and reported the bone union rate as 89% after an average follow-up of 1 year [ 21 ]. Josef et al performed ESWT in 17 long-bone (tibia-femur) pseudoarthrosis patients and had a bone union rate of 64.7% [ 22 ]. Zelle reported had a 76% bone union rate, which was higher in the hypertrophic pseudoarthrosis in the 10 studies including 924 delayed unions treated with ESWT they reviewed to assess the efficacy of ESWT [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, creates hematoma formation, cell death, and bone formation (Table 4) [75]. The review of the literature shows that ultrasounds could have a beneficial effect on the healing of fractures [75][76][77][78][79][80][81][82][83][84][85][86]. A study compares patients with delayed unions after long bone fixation, and the authors, by the application of nails, achieved a union rate of 60%.…”
Section: Extracorporeal Shockwave Therapy (Eswt)mentioning
confidence: 99%
“…A study compares patients with delayed unions after long bone fixation, and the authors, by the application of nails, achieved a union rate of 60%. In comparison, in another group, they chose a combination of dynamization and ultrasound, and the union rate increased to 88% [ 85 ]. The application of shockwave ultrasound to fractures is necessary to be performed in an operating room under fluoroscopic control, and patients should be required to undergo general or regional anesthesia.…”
Section: Reviewmentioning
confidence: 99%
“…The technique of intramedullary nail dynamization is well-established and widely used in clinical practice due to its simplicity [28,[69][70][71][72][73][74][75][76]. However, the effectiveness of intramedullary nail dynamization in treating bone healing disorders has been reported with conflicting results in various studies (Additional file 1: Table S1).…”
Section: Intramedullary Nails Dynamizationmentioning
confidence: 99%
“…The NUSS score could theoretically help predict which bone disorders could benefit more from dynamization, as low NUSS scores are associated with higher success rates. A study by Stolberg et al [ 71 ] demonstrated that NUSS scores are a relevant factor in the success of dynamization for bone non-unions. However, more clinical studies on the NUSS score and dynamization are needed to establish the effectiveness of this treatment approach for bone non-unions.…”
Section: Indications For Dynamizationmentioning
confidence: 99%